Hubungan Gravida, dukungan keluarga dan Frekuensi Kunjungan ANC dengan Kejadian Kekurangan Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Tanjung Batu - Anggraini, Rani; Farida, Tuti; Afrika, Eka; Romadhon, Muhammad (NHM PRESS, 2023)
One of the indicators of sustainable development in 2030 or what is commonly called the Sustainable Development Goals (SDGs) is the implementation of good health. The purpose of these indicators is to ensure healthy lives and promote well-being for all people at all ages. One of the targets that can be measured is a decrease in the Maternal Mortality Rate. In 2021, out of 34 provinces, out of 4,656,382 pregnant women whose upper arm circumference (LILA) was measured, it is known that around 451,350 pregnant women have small LILA 23.5 cm (experiencing risk of CED). The purpose of this study was to determine the relationship between gravida, family support and frequency of ANC visits simultaneously with the incidence of chronic energy deficiency (KEK) in pregnant women in the working area of the Tanjung Batu Health Center in 2023. Type and design of the research is quantitative using an analytic survey method with a cross approach sectional. all pregnant women visiting and carrying out pregnancy checks at the Tanjung Batu Health Center in 2023, totaling 410 respondents. The sample used amounted to 79 respondents. The results of the univariate analysis obtained from 79 respondents, there were 14 respondents (17.7%) who experienced SEZ and 65 respondents (82.3%) who did not experience SEZ. The results of the chi-square statistical test for the Gravida variable obtained ρ value = 0.013, the family support variable ρ value = 0.011 and the ANC visit frequency variable ρ value = 0.009 less than α = 0.05 indicating that there is a significant relationship between gravida and the incidence of CED in the region work of the Tanjung Batu Health Center in 2023. Suggestions It is hoped that health workers, especially midwives, can pay attention to nutritional problems in pregnant women (KEK) by providing education through health education, mentoring and supervision of mothers who experience CED.